Physiopathology of Atypical Evolutions of Idiopathic Focal Epilepsies in Childhood - Van Bogaert, Patrick (Journal of Pediatric Epilepsy, 2016)
This article aims to discuss if the underlying etiology is an important determinant of atypical evolution of idiopathic focal epilepsy (IFE) in childhood and if there might be biomarkers that would predict atypical evolution. It appears that the determinants of atypical evolution remain largely unknown but that both genetic and epigenetic factors are likely to be involved. The analysis of scalp electroencephalography remains the best biomarker of atypical evolution. However, functional neuroimaging methods of investigation are helpful to better understand how epileptic activity affects brain functioning at rest and during goal-directed tasks and to delineate the extent of brain networks that are impaired by epileptic activity. Moreover, neuroimaging bring new arguments favoring the idea that typical and atypical IFE should not be viewed as distinct entities but as a unique syndrome with various degrees of severity that should be treated using tailored strategies and robust biomarkers of efficacy.
Keywords: epilepsy; focal; genetics; childhood; physiopathology; functional neuroimaging